Finisterra e os modos de povoar uma paisagem: estratégias de configuração da perspectiva narrativa - Silva, Gisele Caroline Seeger da (2020)
In the present thesis, we propose to study the configuration of the narrative perspective of Finisterra. Paisagem e Povoamento (1978), by Carlos Oliveira. In the introductory chapter, we propose a review of the critical fortune of the work. In the second chapter, in the light of the assumptions of the so called post-classical narratology, or narrative studies, according to the designation proposed by Carlos Reis (2016), we intend to present the points within which the structural complexity of the perspective in this romance resides. In the third chapter, we address the relations between perspective and character, time and space. In dealing with the relations between perspective and character, we attend to the figuration apparatuses and to the modes of interaction between the different represented perspectives. We maintain that the quality (sensory, affective, imaginative) of the focusers’ perception plays an important role in the (dis)figuration of the characters and that the mode of coordination of the different different worldviews projected by individual perspectives allows the reader to infer the ideological senses with which the work commits itself. In dealing with the relations between perspective and time, we focus on the process of temporal indifferentiation operated in Finisterra, locating its main trigger in the projection of a “time of representation”, in which historical time and even durative time, dependent on the perception of a self, are weakened. Finally, when considering the relation between perspective and space, we look especially over the notion of landscape. We propose that all represented spaces function as constructs of the characters’ perception, being understood only through their mutual articulation. The study allows to verify that the elaborated work on the narrative perspective have effects on the figuration of the characters, the time and the space, delineating a large part of the semantic content and the axiological vectors of the work.